Implants for surgery - Measurements of open-circuit potential to assess corrosion behaviour of metallic implantable materials and medical devices over extended time periods (ISO 16429:2004, IDT) - Abdul Razak, Noor Hayati; Yaakop, Salbiah; Choon, David; Goonting, Tracy E.; T, Mahadevan; Law, Ching Yee; How, Kim Chuan; Singh, Harwant; Ismail, Zulkhairnain; Manickam, Thirumal; Yaakob, Mohd Amin; Mohd Yusof, Hyzan; et al. (Department of Standards Malaysia, 2011)
ISO 16429:2004 specifies a test method for measurements over extended time periods of the open-circuit potential of implant materials and surgically implantable devices immersed in a test environment related to body fluid, using a standard corrosion test cell to study the electrochemical corrosion properties of the devices.